(untitled) (Jurnal Ipteks Terapan, 2023)
The research aims to produce valid and practical motion graphic-based learning multimedia for ICT subjects. This research uses research and development methods by applying the ADDIE model which includes five stages, consisting of analysis, design, development, implementation and evaluation. Data collection tools use validation sheets and questionnaires. Data analysis by conducting product validity tests involving experts consisting of media and material experts. The practicality test involved 32 students of SMA Negeri 1 Payakumbuh. The results of the validity test in this study obtained a score of 92% in the very valid category and the practicality test for students obtained a score of 90% in the very practical category. From the results of this research, it can be concluded that ICT multimedia learning based on motion graphics is appropriate and can be used by students in learning.